Freehand Drawing and Architectural Expression - Hanif Budiman; Ibrahim Numan; Noor Cholis Idham (Journal of Architectural Research and Design Studies, 2021)
The aspect of expression is very important in design ideas, amidst the pressure of programming and procedural thoughts nowadays. The expression is a performance that was born from the deepening of a strong identity that makes us further involvement. Freehand drawing is believed to be an important activity that cannot be separated from an architectural design process. Freehand drawing is proven to be an effort that will increase awareness to produce creative thoughts that remain logical. The natural and organic character of a freehand drawing with its flexibility will be able to express the unique value of each design idea. It is very different when compared to the stereotypical technical line of mechanics. This paper aims to discuss the role of freehand drawing in improving the quality of expression during the design process. The discussion was carried out through a qualitative descriptive analysis based on the experience of carrying out freehand drawing courses and several freehand drawing learning and practices. The topic of the role of freehand drawing in the digital age is very strategic because it reminds us of the importance of the role of balance cognition for the design process in general.Keywords: design; expression; freehand drawing; identity.